Assistance In Preparing EMKM Standard Financial Statements for MSMEs In The Ulujadi Sub-District, Palu City - Syafaat, Muhammad; Pakawaru, Irham; Amalia, Rizki; Riefma, Noer; Arif Hidayatullah,; Andini,; Nurjihan Nadima, (Journal of Community Service: In Economics, Bussiness, and Islamic Finance, 2024)
The continuity of MSMEs is supported by sound financial management. Financial records play a role in business management to assist owners in making financial decisions. Assistance activities for preparing financial statements are carried out to provide new insights into financial records. Assistance is carried out by directly visiting MSME owners and helping to prepare financial reports. The results of the mentoring activities found that MSME owners did not have adequate financial records. Assistance activities help prepare financial reports according to data availability and have not been prepared according to EMKM standards